A short history of anti-rheumatic therapy. III. Non steroidal anti-inflammatory drugs - P. Marson (Reumatismo, 2011)
The chemical advances of the 20th century led to the synthesis of non steroidal anti-inflammatory drugs (NSAIDs), beginning from phenylbutazone and indomethacin and continuing with other new drugs, including ibuprofen, diclofenac, naproxen, piroxicam and, more recently, the highly selective COX-2 inhibitors (coxibs). This progress derived from the discovery of the mechanism of action of these drugs: the inhibition of synthesis of prostaglandins due to the cycloxigenase enzyme system, according to the experimental contributions of John R. Vane.